A role of zinc‐finger protein 143 for cancer cell migration and invasion through ZEB1 and E‐cadherin in colon cancer cells. Issue 1 (5th September 2013) - Paek, A Rome; Lee, Chang‐Hoon; You, Hye Jin; DiGiovanni, John
Abstract To investigate the role of zinc‐finger protein 143 in cancer cells, we stably introduced ZNF143 expression knockdown by infecting colon cancer cells with short hairpin (sh) RNA‐lentiviral particles against ZNF143 (HCT116 sh‐ZNF143). Compared to sh‐control cells, HCT116 sh‐ZNF143 cells showed faster wound healing, increased migration through Transwell chambers, and increased invasion through Matrigel in Transwell chambers. ZNF143 knockdown increased transcriptional expression of ZEB1. Additionally, ZNF143 regulated E‐cadherin transcriptional expression. Small interfering‐RNA‐mediated silencing of ZEB1 expression affected motility in HCT116 sh‐ZNF143 cells. These data suggest that ZNF143 is involved in cellular motility through a ZEB1‐E‐cadherin‐linked pathway in colon cancer cells. © 2013 Wiley Periodicals, Inc.